Fund-mapping: the investment of public resources in the well-being of children and young people in Northern Ireland. Issue 4 (2nd October 2018) - Kemp, Frances; Ohlson, Cassandra; Raja, Anam; Morpeth, Louise; Axford, Nick
ABSTRACT: Across Europe many states are experiencing severe pressures on public services, both from escalating need and from diminishing budgets. As a result, there is increasing interest in understanding how much is spent on services for children and to what effect. All government departments and selected voluntary organisations in Northern Ireland were asked to share financial information about expenditure on services for children and families in the financial year 2012–2013. Respondents were also asked to list evidence-based programmes (EBPs) being implemented and the annual cost in 2012/13. In 2012/13, £2.28 billion was invested in services for children, young people and their families (on average £5, 175 per child). This was spread across 10 departments, with the majority spent by the Department of Education (£1.64 billion, 72%). The split across levels of intervention was 57% prevention (mostly education), 13% early intervention and 19% treatment and maintenance (mostly social care). Unit costs ranged, from £79 for health visiting to £36, 730 for youth custody. Government departments were generally unaware of whether there was any expenditure on EBPs. The routine collection and analysis of cost data can be improved and there is a benefit to be had from (1) decommissioning services that are ineffective or not cost beneficial to release resource for reinvestment, and (2) re-deploying a proportion of the time of staff who work directly with children to more effective activities.